Modulation of Airway Epithelial Innate Immunity and Wound Repair by M(GM-CSF) and M(M-CSF) Macrophages - Sander van Riet; Annemarie van Schadewijk; Steve de Vos; Nick Vandeghinste; Robbert J. Rottier; Jan Stolk; Pieter S. Hiemstra; Padmini Khedoe (Karger Publishers, 2020)
Airway epithelial cells and macrophages participate in inflammatory responses to external noxious stimuli, which can cause epithelial injury. Upon injury, epithelial cells and macrophages act in concert to ensure rapid restoration of epithelial integrity. The nature of the interactions between these cell types during epithelial repair is incompletely understood. We used an in vitro human coculture model of primary bronchial epithelial cells cultured at the air-liquid interface (ALI-PBEC) and polarized primary monocyte-derived macrophages. Using this coculture, we studied the contribution of macrophages to epithelial innate immunity, wound healing capacity, and epithelial exposure to whole cigarette smoke (WCS). Coculture of ALI-PBEC with lipopolysaccharide (LPS)-activated M(GM-CSF) macrophages increased the expression of DEFB4A, CXCL8, and IL6 at 24 h in the ALI-PBEC, whereas LPS-activated M(M-CSF) macrophages only increased epithelial IL6 expression. Furthermore, wound repair was accelerated by coculture with both activated M(GM-CSF) and M(M-CSF) macrophages, also following WCS exposure. Coculture of ALI-PBEC and M(GM-CSF) macrophages resulted in increased CAMP expression in M(GM-CSF) macrophages, which was absent in M(M-CSF) macrophages. CAMP encodes LL-37, an antimicrobial peptide with immune-modulating and repair-enhancing activities. In conclusion, dynamic crosstalk between ALI-PBEC and macrophages enhances epithelial innate immunity and wound repair, even upon concomitant cigarette smoke exposure.